Clinical pathological and molecular features of 100 patients with gastric-type cervical adenocarcinoma - Shangshu Gao; Yan Song (Diagnostic Pathology)
Abstract Objective To investigate the clinicopathological and molecular features, diagnosis, and differential diagnosis of gastric-type cervical adenocarcinoma (GAS). Methods A retrospective analysis was conducted on 100 patients diagnosed with GAS at the National Cancer Center/National Clinical Research Center for Cancer/Cancer Hospital, Chinese Academy of Medical Sciences, from January 2017 to January 2025. Clinicopathological data, histological characteristics, and immunohistochemical expression patterns were analyzed. Targeted next-generation sequencing (NGS) was performed on 11 cases. Results The cohort comprised 100 GAS patients (median age 50 years). Common clinical manifestations included abnormal uterine bleeding and vaginal discharge, with a significant proportion presenting at advanced FIGO stages (II-IV). Histological features were characteristic, and immunohistochemistry, including markers like MUC6, p16, PAX8, and PAX2, was crucial for diagnosis and differential diagnosis. Molecular analysis of 11 cases revealed a distinct high-frequency somatic mutation profile, including TP53 (72.7%), KRAS (45.5%), SMAD4 (45.5%), CDKN2A (36.4%), PIK3CA (27.3%) and STK11 (18.2%). This profile showed molecular homology with pancreaticobiliary adenocarcinoma and was characterized by microsatellite stable (MSS) and low tumor mutational burden (TMB). Regarding molecular markers and prognosis, aberrant p53 expression was frequent (50%, 37/74) but showed no significant association with clinicopathological factors or survival outcomes (p > 0.05). In contrast, PD-L1 expression (CPS ≥ 1) was significantly associated with higher FIGO stage (p = 0.021) and shorter progression-free survival (PFS) (p = 0.046). Conclusions GAS is a highly malignant, HPV-independent cervical adenocarcinoma characterized by atypical clinical symptoms and complex histology. This study, representing a large cohort from Northern China, provides comprehensive insights into its clinicopathological and molecular landscape. We characterized its unique molecular profile and, importantly, identified PD-L1 (CPS ≥ 1) as a potential prognostic marker associated with shorter PFS. These findings contribute to improving diagnosis, understanding biological behavior, and identifying potential therapeutic targets for this aggressive subtype.